POSSIBILITIES OF MULTIDETECTOR COMPUTED TOMOGRAPHY IN THE DIAGNOSIS OF MECKEL DIVERTICULUM - A. L. Yudin; E. A. Yumatova; A. A. Uchevatkin; R. Kh. Azimov; D. S. Mel’chenko (Вестник рентгенологии и радиологии, 2017)
Meckel’s diverticulum is a common congenital anomaly of the gastrointestinal tract, manifested by complications such as gastrointestinal bleeding, intussusception, intestinal obstruction and diverticulitis. Frequency of Meckel diverticulum and its complications is very variable and the diagnosis is usually established intraoperatively. With the development of computed tomography it became possible to identify and differentiate the disease and its complications in the preoperative stage. In this article clinical cases devoted to the diverticulum of Meckel are studied. All patients underwent computed tomography before surgery according to which diverticula complicated by inflammation and bleeding were found.